DISPLACED COMMERCIAL RISK AND ITS EFFECT ON ISLAMIC BANK CUSTOMER LOYALTY: AN ANALYSIS OF SUPPORTING FACTORS - Damayanti, Umi Rachmah; Nirmala, Ade Ria; Nurani, Ratna (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
The purpose of this study is to determine what factors encourage the emergence of Displaced Commercial Risk in Islamic banks and their effect on the loyalty of Islamic bank customers. Displaced Commercial Risk is a risk that occurs due to changes in the level of returns provided by banks to customers, resulting in indications that customers move some of their funds from Islamic banks to conventional banks. This study uses multiple linear regression analysis, by conducting reliability and validity tests, classical assumption tests and hypothesis testing. The sample of this research is Islamic Bank customers who have met the sample determination criteria of 150 respondents. The results showed that there are three factors driving the emergence of Displaced Commercial Risk in Islamic banks, namely the Return Rate, Islamic Bank Operations and Return Expectations. Of the three factors, the Expectation of Yield factor does not have a significant effect on the loyalty of Islamic Bank customers.